Individuals experiencing disability and the ableist physical literacy narrative: critical considerations and recommendations for practice - Pushkarenko, Kyle; Howse, Elizabeth; Gosse, Nicholas (Frontiers in Sports and Active Living, 2023)
Physical literacy (PL) has been readily accepted and integrated globally, including organizations affording services to individuals experiencing disability. Despite its uptake, recent research has illustrated that understandings of PL reflect the normative standards of those who do not experience disability, leading to practices that diminish the unique and embodied capability of others while simultaneously validating ableism. While a shift towards recognizing and valuing the heterogeneity associated with PL has recently occurred, the ableist narrative persists. As a result, the operationalization of PL directly contradicts its conceptualization, fostering a physical activity climate that continues to marginalize individuals experiencing disability. With this in mind, this paper critically unpacks PL, challenging the existing ableist narrative and offering suggestions to heighten the level of inclusivity that underscores PL. Pathways, where physical activity professionals contribute to reproducing ableism, will be discussed.